Seamless model interoperability for software design and analysis - M. A., Ameedeen; Thong, Weng Jie (Publishing Technology, 2017)
Software development has now become a critical process that handles a plethora of sensitive and mission critical information that involves lives, money and time. As such, designing such a critical piece of software has become even more critical and requires a solid logical or mathematical analysis behind it to ensure the reliability of the software. Modelling is one of the preferred methods for software designers to express their design, especially through easy to use modeling languages such as UML (Unified Modelling Language). However the lack of formal analysis capabilities in UML makes it necessary for a redundant formal model to be created as well, in order to analyze the design. Model interoperability as referred to in this paper promotes the use of UML, to be paired seamlessly with a formal model that is capable in performing formal mathematical analysis on the software design.